CITA HUKUM BANGSA DAN NEGARA INDONESIA DALAM KONTEKS RENCANA PEMBANGUNAN JANGKA PANJANG NASIONAL 2005-2025 (Faculty of Law, University of Palembang, 2023)
Revisions were made to the Republic of Indonesia's 1945 Constitution, and the modifications had a profound impact on how the Indonesian state government was organized. The modification of the state's institutional structure for upholding legal norms that took place in Indonesia's political system after the end of the New Order era was a key stream of reform thinking. In the Indonesian state administration system, reform means strengthening the presidential system. The president's dual roles as head of state and head of government are at the heart of the presidential system of government (head of state). A normative and conceptual approach are combined in the study's explanatory technique. The state's experience with long-term development plan implementation is notably due to the third amendment to Article 3 of the Constitution of the Republic of Indonesia, which changed it to Article 3 Paragraph (1) and deleted the People's Consultative Assembly's jurisdiction. Use RI to generate the GBHN. The RPJPN was created in place of the GBHN as a framework for national development as part of the Decentralization and Regional Autonomy System implementation in order to address concerns regarding the president's latitude. Realizing the goals and aspirations of the nation and state is the primary goal of national development, according to the Preamble of the Constitution of the Republic of Indonesia.